Dissecting the biology of allogeneic HSCT to enhance the GvT effect whilst minimizing GvHD - Blazar, Bruce R. (Nat Rev Clin Oncol, 2020)
Allogeneic haematopoietic stem cell transplantation (allo-HSCT) was the first successful therapy for patients with haematological malignancies, predominantly owing to graft-versus-tumour (GvT) effects. Dramatic methodological changes, designed to expand eligibility for allo-HSCT to older patients and/or those with co-morbidities, have led to the use of reduced-intensity conditioning regimens, in parallel with more aggressive immunosuppression to better control graft-versus-host disease (GvHD). Consequently, disease relapse has become the major cause of death following allo-HSCT. Hence, the prevention and treatment of relapse has come to the forefront and remains an unmet medical need. Despite >60 years of preclinical and clinical studies, the immunological requirements necessary to achieve GvT effects without promoting GvHD have not been fully established. Herein, we review learnings from preclinical modelling and clinical studies relating to the GvT effect, focusing on mechanisms of relapse and on immunomodulatory strategies that are being developed to overcome disease recurrence after both allo-HSCT and autologous HSCT. Emphasis is placed on discussing current knowledge and approaches predicated on the use of cell therapies, cytokines to augment immune responses and dual-purpose antibody therapies or other pharmacological agents that can control GvHD whilst simultaneously targeting cancer cells.